First naxal:an authorised biography of Kanu Sanyal - Bappaditya Paul (Sage, 2014)
It seldom happens that the story of an individual becomes so intertwined with the cause she or he stands for that it becomes impossible to separate the one from the other. Kanu Sanyal’s is one such rare story: to read it is to relive the history of the Naxalite Movement, which the Indian establishments call the country’s biggest internal security threat.